1994
DOI: 10.1111/j.1574-6976.1994.tb00140.x
|View full text |Cite
|
Sign up to set email alerts
|

Degradation of halogenated aliphatic compounds: The role of adaptation

Abstract: A limited number of halogenated aliphatic compounds can serve as a growth substrate for aerobic microorganisms. Such cultures have (specifically) developed a variety of enzyme systems to degrade these compounds. Dehalogenations are of critical importance. Various heavily chlorinated compounds are not easily biodegraded, although there are no obvious biochemical or thermodynamic reasons why microorganisms should not be able to grow with any halogenated compound. The very diversity of catabolic enzymes present i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2000
2000
2014
2014

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(8 citation statements)
references
References 109 publications
(100 reference statements)
0
8
0
Order By: Relevance
“…Another biotic factor that can significantly affect the in situ bioremediation process is 'adaptation of degradative microorganism(s) towards environmental stresses' (Fiorenza & Ward, 1997;Rittmann et al, 2001;Somova et al, 2005). The in situ application of microorganisms exposes them to diverse stresses that can lead to a major decline in the survival of the degradative microbial strain as well as the efficiency of the pollutant removal (Pries et al, 1994). One of the most common stresses encountered during in situ bioremediation is the elevated concentrations of target pollutant and cross-contamination of other nontargeted pollutants (Lee & Lin, 2006).…”
Section: Biotic Factorsmentioning
confidence: 99%
“…Another biotic factor that can significantly affect the in situ bioremediation process is 'adaptation of degradative microorganism(s) towards environmental stresses' (Fiorenza & Ward, 1997;Rittmann et al, 2001;Somova et al, 2005). The in situ application of microorganisms exposes them to diverse stresses that can lead to a major decline in the survival of the degradative microbial strain as well as the efficiency of the pollutant removal (Pries et al, 1994). One of the most common stresses encountered during in situ bioremediation is the elevated concentrations of target pollutant and cross-contamination of other nontargeted pollutants (Lee & Lin, 2006).…”
Section: Biotic Factorsmentioning
confidence: 99%
“…Inorganic materials, predominantly aluminas and silicas, have been commonly used as enzyme carriers because of their low cost, large surface area to volume ratio, favorable surface chemistry, and formability. In many studies involving similar haloalkane dehalogenases isolated from various bacteria (Janssen et al, 1985;Pries et al, 1994, Van den Wijngaard et al, 1992, each has demonstrated an activity optimum between pHs 8.2 and 9.5. Inorganic alumina supports perform well under these basic reaction conditions (Hyndman et al, 1992a(Hyndman et al, , 1992b.…”
Section: Introductionmentioning
confidence: 99%
“…Rate measurements showed that haloalkane dehalogenase had an activity with various C1 and C2 haloalkanes (Table 2) that is slightly lower than the rate found with 1,2-dichloroethane, which was 4.9 lmol of substrate per min per mg of protein, close to the value of 6 lmol min )1 mg )1 found by Pries et al (1994). Especially compounds containing a carbon-bromine bond were rapidly converted.…”
Section: Dehalogenation Of Bcm Bce and Cfe By Haloalkane Dehalogenasementioning
confidence: 66%